تفاعلية التشبيه في مسرح التعزية - حسين, فلاح كاظم (lark, 2019)
The data of Theatrical field has awarded freedom to the Thoughts of dramatic shows in public and prsvate levcls , after being prohibited during the tyrannical regime.The research tachles the Processes of intensified narration and identifying the painful events of Imam incident , and presenting it in dramatic modes at variance with the traditional presentation in term of scenario, production , performance and Theatrical techniques , Threfore the researcher has Com up with a research problem titied " The Interactivity of Similitude in Consolaion Theater " . The research has attempted to mare the reader realizing the interactional rapport betweer I mam Hussein incident and the audience in Scientific and systematic mode.([i])    [i]-   ترجمة : مهدي عباس محسن, تخصص في علم الاسلوب للغة الانكليزية , كلية الامام الكاظم (ع) للعلوم الاسلامية الجامعه, ساعه 11.30 صباحاً, من يوم الخميس – 19 \ 5 \2016.